How do extended benefits affect unemployment duration? A regression discontinuity approach - Rafael Lalive (Institute for Labour Market Policy Evaluation (IFAU), 2006)
This paper studies a program that extends the maximum duration of unemployment benefits from 30 weeks to 209 weeks. Interestingly, this program is targeted to individuals aged 50 years or older, living in certain eligible regions in Austria. In the evaluation, I use sharp discontinuities in treatment assignment at age 50 and at the border between eligible regions and control regions to identify the effect of extended benefits on unemployment duration. Results indicate that the duration of job search is prolonged by at least .09 weeks per additional week of benefits among men, whereas unemployment duration increases by at least .32 weeks per additional week of benefits among women. The salient differences between men and women are consistent with the lower minimum age for early retirement applying to women.
Keywords: C41; J64; J65; 330; benefit duration; unemployment duration; early retirement; regression discontinuity; Arbeitslosigkeit; Lohnersatzleistungen; Dauer; Ältere Arbeitskräfte; Flexible Altersgrenze; Schätzung; Österreich